Airports’ Operational Performance and Efficiency Evaluation Based on Multicriteria Decision Analysis (MCDA) and Data Envelopment Analysis (DEA) Tools - Jardim, João; Baltazar, Maria Emília; Silva, Jorge; Vaz, Margarida (Journal of Tourism, Sustainability and Well-being, 2015)
Airport benchmarking depends on airports’ operational performance and efficiency indicators, which are important for business agents, operational managers, regulatory agencies, airlines and passengers. There are several sets of single and complex indicators to evaluate airports’ performance and efficiency as well as several techniques to benchmark such infrastructures. The general aim of this work is twofold: to balance the data envelopment analysis (DEA) and multicriteria decision analysis (MCDA) tools and to show that airport benchmarking is also possible using a multicriteria decision analysis tool called Measuring Attractiveness by a Categorical Based Evaluation Technique (MACBETH). Whilst DEA measures the relative performance in the presence of multiple inputs and outputs, MCDA/ MACBETH uses performance and efficiency indicators to support benchmark results, being useful for evaluating the real importance and weight of the selected indicators. The work is structured as follows: first, a state-of-the-art review concerning either airport benchmarking and performance indicators or DEA and MCDA tool techniques; second, an overview of the impacts on airports’ operational performance and efficiency of emergent operational factors (sudden meteorological/natural phenomena); third, two case studies on a set of worldwide airports and Madeira (FNC) Airport; and fourth, some insights into and challenges for future research that are still under development.